Impact and management of physiological calibration in spectral analysis of blood pressure variability - Kiviniemi, Antti M.; Hintsala, Heidi; Hautala, Arto J.; Ikäheimo, Tiina M.; Jaakkola, Jouni J.; Tiinanen, Suvi; Seppänen, Tapio; Tulppo, Mikko P. (Frontiers in Physiology, 2014)
Physiological calibration (Physiocal) improves the quality of continuous blood pressure (BP) signal from finger. However, the effects of Physiocal on spectral characteristics of systolic BP (SBP) variability are not well-known. We tested the hypothesis that the use of Physiocal may alter the results on SBP variability when compared with BP recording without Physiocal. Continuous BP was recorded simultaneously from fingers of both arms during 10-min standing by two Nexfin devices, one with (ON) and the other without (OFF) Physiocal (n=19). Missing SBP values in ON signal were linearly interpolated over Physiocal sequences (ON_inter). The OFF signal was analyzed without any corrections (OFF_reference) and after linear interpolation of corresponding sequences when Physiocal appeared in the ON signal (OFF_inter). Mean low frequency power of SBP oscillations (LF_SBP, 0.04-0.15 Hz) did not differ between the OFF_reference, OFF_inter and ON_inter. However, LF_SBP deviated more from OFF_reference when analysed from ON_inter compared with the analysis from OFF_inter (median [interquartile range]: 14.7 [4.6-38.6] vs. 0.9 [0.5-1.8] %, p<0.05). In conclusion, the use of Physiocal had a significant effect on the spectral SBP variability that overwhelms the impact of linear interpolation of short data sequences. Therefore, caution is needed when comparing SBP variability between BP datasets acquired with and without Physiocal.